Tax literacy of employees in Sarawak in the light of the self assessment system / Nero Madi and Amrizah Kamaluddin (Universiti Teknologi MARA, Sarawak, 2005)
This study intends to gauge the general level of tax literacy of public and private sectors employees in the event of the implementation of the Self Assessment System (SAS) for salaried individuals in 2004. Under SAS, the taxpayers are expected to be functionally literate to compute their own tax liabilities. The study explores the relationship between tax literacy and some of the demographic factors such as employment sectors and location of workplace. The study also investigates the taxpayers' awareness of issues relevant to SAS. Statistical results using One-way ANOVA analysis, inter alia, show that taxpayers in the corporate sector were as literate as their counterparts in the public sector. There was no significant difference in the mean level of tax literacy scores between employees in the two sectors. Similarly, there was no significant relationship between working experience and tax literacy. The results of the study hinted that salaried taxpayers might not be prepared for SAS for at least one or two years of assessments.